Optical Coherence Tomography Angiography Parameters Correlated to the Growth of Macular Neovascularization in Age-Related Macular Degeneration - Arrigo, Alessandro; Amato, Alessia; Mularoni, Cecilia; Saladino, Andrea; Aragona, Emanuela; Pina, Adelaide; Calcagno, Francesca; Bandello, Francesco; Battaglia Parodi, Maurizio (Frontiers in Physics, 2022)
Background: To investigate optical coherence tomography angiography (OCTA) quantitative pa-rameters associated with macular neovascularization (MNV) size modifications in age-related macular degeneration. Methods: Study design was prospective, with 1-year of follow-up. All the included MNV eyes were treated by anti-VEGF intravitreal injections. Quantitative OCTA parameters, including MNV vessel tortuosity (VT) and MNV reflectivity, were calculated. Post-hoc analyses assessed the cor-relation between quantitative OCTA metrics and MNV size modifications. Results: A total of 28 MNV eyes of 28 patients were included. Baseline LogMAR BCVA was 0.36±0.21 LogMAR, improved to 0.28±0.22 Log-MAR after 1-year (p<0.01), with a mean number of 8±3 anti-VEGF injections. Eyes characterized by high MNV VT values group showed worse outcome and higher increases of MNV size. A mean MNV reflectivity value of 101 was associated with a high probability of changes in MNV size. MNV growth was also influenced by the type of MNV, with type 2 and mixed type lesions showing increases in MNV size, unlike type 1 MNV. These factors showed a cumulative effect in determining MNV size modifications. In most of the cases, we observed MNV size increases. Conversely, MNV lesions characterized by low MNV VT values may experience size reductions over the follow-up (34% of cases). The number of intravi-treal injections had no significant influence on MNV size changes. Conclusions: Quantitative OCTA allowed to discriminate highly perfused MNV lesions, providing a basis to predict MNV size modifications and the direction of MNV expansion.